Aging Effects on a Driver Position Sensor Integrated into a Woven Fabric - Marc Martínez-Estrada; Ignacio Gil; Raúl Fernández-García (Sensors)
A textile woven presence sensor was previously presented to demonstrate its functionality in eliminating some false positives on car seat presence sensors. After studying the functionality, the next characteristic that the textile sensor should demonstrate is its reliability. The woven sensor was prepared to be tested against ageing. The ageing cycle was prepared according to the UNE-EN ISO 17228:2015 standard. Nine woven sensors are prepared, seven of them face the aging test, and two are selected as reference sensors. The characterization of the woven sensor has been carried out through a microcontroller measurement circuit that obtains the cycles to charge the sensor. Comparison of the results obtained shows that the effects of ageing are negligible. The behavior of the aged sensors is similar to that of the reference sensors, indicating that the variations in the values of both aged and reference sensors are provoked by the environmental conditions during the measurements. To support this argument, a statistical study based on a t-Student analysis was carried out. After 4 ageing cycles, the functionality of the sensors remains unaffected. This research proves the reliability of the woven textile sensor, which encourages its use in automotive applications.